His Master’s Voice: Sound Devices in Bram Stoker’s Dracula - Maria Parrino (Cahiers Victoriens et Edouardiens)
One year after the publication of Dracula (1897), the English photographer Francis Barraud was commissioned a painting from his picture of a dog looking at and listening to a cylinder phonograph. His work, entitled His Master’s Voice, became one of the most famous logos in the world. Barraud’s painting was particularly meaningful for not only did it raise the issue of the amplified voice, but it also visualized the impact and effect that technological instruments had on the amplified voice. The phonograph shows how voices can become disconnected from the material body and raises the issue of what actually constitutes a voice. Among the modern technological devices mentioned in Bram Stoker’s Dracula, the phonograph plays an important role, a presence which is both disconcerting and reassuring. The power and the uncanny effect of the disembodied voice is evident in Mina’s reaction to Dr Seward’s phonographic recording, a ‘wonderful’ and ‘cruel’ device as it records not only the speaker’s voice but also its tone, thus revealing bodily sounds which writing, instead, hides. In Dracula, the distinction between speech and writing is constantly under pressure: on the one hand, the characters’ urge to write (journals, letters, etc.), on the other there is an agency of oral interaction. From Renfield’s calling in of the vampire (a master who needs a servant to be welcomed in), to Dracula’s attempt at mastering oral English in order to conceal his foreignness, the novel proves to be an important example of how literature deals with sound devices.